Evaluation of Higher Education in Brazil: discourses, practices and disputes (Práxis Educativa, 2017)
This text analyzes the field of Higher Education, taking as the subject-object of investigation the evaluation policies, the positioning and the engagement of certain subjects in the formulation and implementation of the evaluation policies of Higher Education, which implies exploring relevant dimensions of the dispute and the structuring of the field of Higher Education in Brazil. The analysis explored documents and publications, as well as movements and positioning of the subjects in the field and in the state sphere. It is argued that the evaluation policies of Higher Education have been permeated by disputes expressed through the positioning of groups that are situated in the field and in the State apparatus - MEC, CONAES, INEP - that have been disputing the field since 1990. Two positions predominate in the field, the discourse and the model of contextual-participatory evaluation and the rational-objectivist. The scenario outlined in recent years allows to observe that the introduction of indexes by state agencies has promoted a turning point in the evaluation policy conduct, realigning it to a rational-objectivist perspective. Keywords: Higher Education. Evaluation policies. Field of Higher Education. Brazil.